2019
DOI: 10.3390/ijms20071685
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Triggered Reversible Phase Transfer of Azobenzene-Based Ionic Liquid Surfactants between Oil and Water

Abstract: The reversible phase transfer of compounds between two immiscible liquid phases has many applications in a wide range of fields, and ionic liquids have been widely used as potential functional solvents and catalysts. However, photo-triggered reversible phase transfer of ionic liquids between the organic phase and water phase has not been reported so far. In the present work, the reversible phase transfer of six kinds of azobenzene-based ionic liquid surfactants between the organic phase and water phase is inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Light stimulus‐response is an attractive method due to the easy availability of the light source, accurate irradiation, convenient operation, and non‐additive to the system. Light‐responsive ILs refer to the light responsive‐ability of photosensitive groups, also known as photosensitive ILs, mainly including azobenzene, [ 52 ] cinnamic acid, [ 53 ] spirogyra, [ 54 ] diarylethene, [ 55‐56 ] etc . The structure of light‐responsive ILs can be changed by light, further affecting the melting point, [ 55,57‐59 ] rheological properties, [ 60 ] hydrophilicity‐hydrophobicity, [ 61 ] and conductivity [ 61‐63 ] of ILs.…”
Section: Light‐responsive Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light stimulus‐response is an attractive method due to the easy availability of the light source, accurate irradiation, convenient operation, and non‐additive to the system. Light‐responsive ILs refer to the light responsive‐ability of photosensitive groups, also known as photosensitive ILs, mainly including azobenzene, [ 52 ] cinnamic acid, [ 53 ] spirogyra, [ 54 ] diarylethene, [ 55‐56 ] etc . The structure of light‐responsive ILs can be changed by light, further affecting the melting point, [ 55,57‐59 ] rheological properties, [ 60 ] hydrophilicity‐hydrophobicity, [ 61 ] and conductivity [ 61‐63 ] of ILs.…”
Section: Light‐responsive Ilsmentioning
confidence: 99%
“…The transfer efficiency was [C 4 AzoC 2 DMEA][Br] > [C 4 AzoC 2 TMA][Br] > [C 4 AzoC 2 MIM][Br] > [C 4 AzoC 2 Py][Br] and [C 4 AzoC 2 DMEA][Br] > [C 4 AzoC 4 DMEA][Br] > [C 4 AzoC 6 DMEA][Br]. [ 52 ] At 25 °C, the yellow azobenzene ionic liquid was dissolved in the upper organic phase, and the lower layer was a transparent aqueous phase in the initial stage. After 30 min of UV light irradiation, the lower aqueous phase became yellow, and the upper organic phase became lighter in color, which indicated that the ionic liquid was partly transferred to the aqueous phase.…”
Section: Light‐responsive Ilsmentioning
confidence: 99%
“…We assigned 18 articles to this thematic area, namely [ 128 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 ]. Their distribution within the typing specified in the Introduction is presented in Table 9 .…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…Taking this circumstance into account, two basic variants of their systematics are possible—by the nature of the transfer (energy transfer or charge transfer) and by the physicochemical nature of the material, in which such a transfer is carried out. In the variant of systematics by the nature of transfer, all articles presented in this Thematic Area can be divided into those in which studies are related to energy transfer, and those in which studies are related to charge transfer; the first include articles [ 128 , 236 , 237 , 238 , 239 , 241 , 242 , 246 , 247 , 249 ], the second, articles [ 235 , 240 , 243 , 244 , 245 , 248 , 250 , 251 ]. In the variant of systematics by the nature of the material, two types of articles can also be distinguished—those in which the energy/charge transfer is carried out in organic materials, namely [ 128 , 236 , 237 , 238 , 240 , 243 , 244 , 247 , 249 , 250 , 251 ], and those in which this transfer is carried out in inorganic materials [ 235 , 239 , 241 , 242 , 245 , 246 , 248 ].…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…It is known that the configuration of the azobenzenebased compound cation can be changed from trans-to cisisomer under UV irradiation in water (Figure S10), leading to a significant enhancement of the hydrophilicity of the ILS, [23] increase of the surface tension of an aqueous solution and reduction of its surface activity. For example, after UV irradiation, the surface tension of 1 10 À3 mol kg À1 [C 4 AzoC 2 DMEA]Br in water increased from 49.6 mN m À1 to 56.3 mN m À1 , and its CAC increased from 2.3 10 À3 to 1.3 10 À2 mol kg À1 (Figure S11).…”
Section: Angewandte Chemiementioning
confidence: 99%